A Muslim Scholar and Diplomat in Baghdad at the Time of the Būyids: The Encounters of al-Bāqillānī within a Multi-Confessional Environment - Muhammed Seyyit Şen (İslam Tetkikleri Dergisi)
The late tenth century witnessed fundamental political and religious transformations in the Muslim world. After emerging as a Shī‘ī Dynasty in Iran in the first half of the tenth century, the Būyids controlled Baghdad in 945 and began to dominate the Sunnī Abbāsid Caliphate. In academia, it is generally believed that the Būyid Dynasty exclusively supported the Shī‘ī faith and popularized Shī‘ī practices while marginalizing and oppressing Sunnism in Iraq. Even though the Būyids were identified with Shī‘ism, different confessional groups (Christians, Mu’tazilīs, Shī‘īs, and Sunnīs) were well-represented in the Būyid court. In addition to encountering the Byzantines diplomatically and culturally, the Būyids were also engaged with Christianity. In my paper, through the life and works of a famous Sunnī theologian, al-Bāqillānī (d. 403/1013), I examine how the Būyids interacted with different religious groups. I also analyze how they established more flexible and porous confessional boundaries rather than engaging in sectarianism and religious conflict.